Pengaruh Financial Technology, Fee-Based Income, dan Biaya Operasional Pendapatan Operasional terhadap Profitabilitas Perusahaan Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia - Shafa Nabilah Putri; Ulfi Pristiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the effect of financial technology, fee-based income, and BOPO on the profitability of Islamic banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research is motivated by the rapid development of digital financial services and the importance of operational efficiency in enhancing the financial performance of Islamic banks. This research employs a quantitative approach with purposive sampling. The data were obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the annual financial reports of Islamic banking institutions. The analysis technique used is multiple linear regression with the assistance of SPSS software. The results show that, partially, financial technology and fee-based income do not have a significant effect on profitability, while BOPO has a negative and significant effect. However, simultaneously, all three variables have a significant effect on profitability. Future studies are expected to include additional relevant variables and extend the observation period